Crime Victims and Their Unmet Civil Legal Needs: Pro Bono Service Provision Among Private Attorneys. Issue 1 (April 2019) - Daigle, Leah E.; Harris, Michelle N.; Mummert, Sadie J.
Crime victims often experience a host of negative consequences. In relation to these consequences, crime victims may also find themselves in need of assistance from the criminal justice system and civil legal service providers. Despite this need, crime victims often lack access to civil legal services. One way to potentially improve the availability and accessibility of civil legal services for crime victims is to increase the provision and availability of pro bono services; however, the way that attorneys perceive pro bono service for crime victims may be an impediment to service provision. Despite this, little is known about how private attorneys view pro bono work with crime victims. We examine how private attorneys view pro bono work with crime victims, the barriers to this service and what may incentivize them to engage in this work by utilizing data from a project assessing the civil legal needs of crime victims in the state of Georgia (USA). We find that a relatively small proportion of private attorneys in Georgia engage in pro bono work with crime victims. Barriers and incentives to pro bono service engagement and implications are discussed.